The importance of the Outdoor Thermal Comfort (OTC) for urban planning. - Tapias, Estefania (FSU, 2019)
Durch die steigende Urbanisierungsrate rücken "Urban Heat Islands" immer stärker in den Vordergrund. Die Veränderungen des Stadtklimas können sich direkt auf den menschlichen Komfort auswirken, welcher mithilfe des OTC-Index (Outdoor Thermal Comfort) gemessen wird und auf thermophysiologischen Bewertungsmethoden beruht. Die Nutzung der so gewonnenen Daten kann die Stadtplanung bei der Entwicklung qualitativer Freiräume unterstützen.

The world is facing unprecedented speeds in climate change leading to an increase in global average temperatures (global warming). The Intergovernmental Panel on Climate Change (IPCC) 2018 special report is the most up-to-date and comprehensive explanation of the science of climate change. The report warns that, at the current rate of warming, the average temperature could increase by another 0.5°C within the next 30 years. It also urges that we need to build upon the solutions available today and focus on massive behavioural and lifestyle changes.
Keywords: Stadtklima; Klimawandel; Hitzebelastung; Mikroklima; Kommunaler Klimaschutz; Klimafolgenanpassung; Wohlbefinden; Lebensqualität; Messmethode